Collaborative Learning in Education : A Bibliometrics Analysis - Syathiri, Balqis (Proceeding International Conference on Religion, Science and Education, 2025)
Currently, more and more teachers decide to follow active teaching methods, leaving behind traditional teaching methods. Among the most used pedagogical methods in the educational field is the collaborative learning. The general objective of the present investigation is to know the performance and academic development of the term "collaborative learning" in the documents collected in the Scopus database. Over the past decade, there has been a significant shift in education towards active teaching methods, with collaborative learning emerging as one of the most widely adopted approaches. This study conducts a bibliometric analysis of publications from the Scopus database between 2014 and 2024, examining the academic development of the term "collaborative learning." The analysis reveals an annual growth rate of 8.84% in publications, indicating a steady increase in interest. The research is highly collaborative, with an average of 3.45 co-authors per article, and 13.79% of the publications involving international co-authorship. The findings demonstrate that collaborative learning enhances critical thinking, creativity, and problem-solving skills, with increasing integration of technology such as e-learning and computer-aided instruction. This study offers a comprehensive overview of the trends and contributions in the field, providing valuable insights for educators and researchers to develop more effective collaborative learning strategies in diverse educational settings.